Performance Changes in Mass and Compressive Strength of High-Calcium Fly Ash Based Geopolymer Concrete Due to Sodium Sulphate Exposure - Tajunnisa, Yuyun; Husin, Nur Achmad; Kusbiantoro, Andri; Daffa Azmi, Ahmad; Fadilah Ashara, Khansa; Shigeishi, Mitsuhiro (IPTEK The Journal of Engineering, 2024)
The sulfate environment is one of the conditions that significantly affect the durability of concrete. Sulfate attack causes cracks and affects the quality of the concrete. Therefore, it is necessary to innovate concrete that can withstand the aggression of this sulfate attack. Geopolymer concrete is a breakthrough that can be developed as an alternative material without using Portland cement as the ingredients, yet by using class F fly ash as the primary source material. On the other hand, the availability of class C fly ash with high CaO content is highly abundant in Indonesia. The high calcium content in this fly ash will cause the fresh geopolymer concrete to harden rapidly. Previous studies used sucrose as an additive to overcome this rapid hardening problem. However, its effect on the geopolymer concrete exposed to sulfate ingression requires further investigation. In this study, the geopolymer concrete was produced by using class C fly ash and sucrose. The sulfate ingression was simulated by immersing the concrete specimen in the sodium sulfate solution while the mass changes and compressive strength were examined. pH measurement of the sodium sulfate solution was also carried out to provide a different perspective on the data analysis. Cylindrical specimens, measuring 10 cm x 20 cm, were produced using the dry-mixing method and the characteristic strength of 28 MPa according to SNI 2847–2019. From the results, geopolymer concrete with sucrose showed a high workability performance through the high slump value obtained. Nevertheless, the experimental results also indicated the declining strength of geopolymer concrete after the sulfate exposure. However, only a slight reduction was observed. The strength residue still satisfies the minimum requirement of SNI 2847-2019. It shows the potential of geopolymer concrete to be used as a construction material in a harsh environment with high sulfate content.